Aluminum electrolytic capacitor powder stacking sintered foil and preparation method thereof

By introducing dielectric substances on the surface of aluminum powder of aluminum electrolytic capacitors using chemical vapor deposition method, the side reactions and carbon residue problems caused by high activity of aluminum powder are solved, and the high electrostatic capacity and safety are improved.

CN119626783AActive Publication Date: 2025-03-14XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411751933.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

During the preparation process, the powder accumulation of aluminum electrolytic capacitors sintered foil is caused by the high activity of aluminum powder and the reaction of some solvents and external environment, which leads to side reactions and carbon residues, affecting the electrostatic capacity and safety.

Method used

Dielectric substances are deposited on the surface of aluminum powder by chemical vapor deposition to avoid direct contact between aluminum powder and dispersant, inhibit side reactions, and control the environment to reduce carbon residue during subsequent degreasing and sintering.

Benefits of technology

The high electrostatic capacity and safety improvement of powder stacking sintered foil of aluminum electrolytic capacitors has been achieved, the problems of side reactions and carbon residues have been solved, and the electrostatic capacity per unit area has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626783A_ABST
    Figure CN119626783A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum electrolytic capacitor powder stacking sintered foil and a preparation method thereof, and belongs to the technical field of aluminum electrolytic capacitors. The preparation method of the aluminum electrolytic capacitor powder stacking sintered foil comprises the steps that aluminum powder and a dielectric substance precursor serve as raw materials, a dielectric substance is deposited on the surface of the aluminum powder through a chemical vapor deposition method, and the aluminum powder wrapped by the dielectric substance is obtained; the dielectric constant of the dielectric substance is greater than that of aluminum oxide; the method comprises the following steps: uniformly mixing aluminum powder wrapped by a dielectric substance, a binder and a solvent, coating an aluminum foil substrate with the mixture, drying, degreasing at 350-550 DEG C in an oxygen-containing atmosphere, sintering at 600-670 DEG C in an oxygen-free state, and energizing after sintering to obtain the aluminum electrolytic capacitor powder stacked sintered foil. According to the aluminum electrolytic capacitor powder stacking sintering foil prepared by the method, the aluminum electrolytic capacitor powder stacking sintering anode foil per unit area has excellent electrostatic capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum electrolytic capacitors, and more specifically to an aluminum electrolytic capacitor powder stacking sintered foil and a preparation method thereof. Background Art

[0002] Compared with other types of capacitors, aluminum electrolytic capacitors have high volume energy density, controllable dielectric layer thickness, self-healing dielectric layer, and can obtain high rated electrostatic capacitance, etc. Therefore, they are widely used in consumer electronics, household appliances, industrial control and other fields. Electrostatic capacitance is the main parameter of capacitors, and the capacitance of anode foil determines the electrostatic capacitance of aluminum electrolytic capacitors, so improving the specific capacitance of anode foil is an effective way to improve electrolytic capacitors.

[0003] At present, the anode foil of aluminum electrolytic capacitors in large quantities on the market is made of electrochemically etched foil. Electrochemically etched foil consumes a lot of electricity during the production process, and is accompanied by the generation of acidic waste liquid, which pollutes the environment; in terms of performance, the anode foil corrosion technology is suffering from a bottleneck, and it is difficult to further break through the electrostatic capacity in a short period of time. Compared with the corrosion foil, the powder stacking sintering foil has a higher specific surface area, and the electrostatic capacity of the powder stacking sintering anode is larger per unit area. However, the powder stacking sintering foil is affected by the activity of aluminum powder during the preparation process, and the binder and dispersant selected at room temperature are limited. Most of the binders soluble in organic systems have high decomposition temperatures. If the degreasing temperature is not enough, the binder is not completely decomposed, and carbon residue is easily caused in the oxygen-free environment during the sintering process, and the residual current after energization is large; if the degreasing temperature is too high, the binder is completely decomposed, and the thermal oxidation film on the surface of the aluminum powder is too thick, which is not conducive to the formation of the sintering neck in the later stage. Some water-based binders have a low decomposition temperature, but aluminum powder reacts with dispersants to hydrate aluminum oxide. High-temperature dehydration affects later sintering and also affects electrostatic capacity. At the same time, hydrogen is produced during the reaction with water, which poses a safety problem. On the premise of reducing the activity of aluminum powder, aluminum powder surface coating is an effective means.

[0004] Common coating methods include solid-phase nanoparticle mixed coating and liquid-phase coating. In the physical mixing and doping of solid-phase nanoparticles, the coating of nano high dielectric constant powder is not dense and easy to fall off, which does not match the sintering temperature of aluminum powder, resulting in the easy fall-off of nano high dielectric constant particles. Nanoparticles are mixed into the sintering neck and reduce the sintering strength. In the liquid-phase coating method, the surface coating is relatively thick, which affects the melting and swelling during the sintering process. The sol-gel contains a large amount of organic matter, which is carbonized in an oxygen-free environment. The dielectric layer is thick and dense, which easily causes carbon residues, and the leakage current of the anode foil formed is large.

[0005] Chinese invention patent CN117594359B describes an aluminum electrolytic capacitor anode sintered foil and its preparation method. Spherical aluminum powder is used as an anode and a titanium target is used as a cathode. An aluminum-titanium composite powder is generated by magnetron sputtering, and the surface of the aluminum-titanium composite powder is coated with a titanium film. Magnetron sputtering bombards the target material with high-energy ions, giving kinetic energy to the target atoms and molecules, and the moving electrically neutral target atoms or molecules are deposited on the substrate to form a thin film. Because the moving target atoms and molecules have poor diffraction, the coverage and uniformity of the film are uncontrollable. After the titanium metal is deposited, the oxide film is not dense after oxidation and cannot prevent the reaction of aluminum powder with the outside world.

[0006] Chinese invention patent CN117373830B describes a method for manufacturing anode foil of aluminum electrolytic capacitors with high dielectric constant composite films. By adding metal oxides with high dielectric constants into aluminum paste, the overall dielectric constant and electrostatic specific capacity of the composite film anode foil are improved. The combination of powder and powder does not reduce the activity of aluminum powder and prevent it from reacting with the outside world. In order to prevent agglomeration caused by surface tension, the introduced surfactant is easily carbonized in a high temperature oxygen-free environment, causing the capacitor to break down and fail. Summary of the invention

[0007] In view of the above problems, the present invention provides an aluminum electrolytic capacitor powder stacking sintered foil and a preparation method thereof. The present invention introduces a dielectric material onto the surface of aluminum powder by chemical vapor deposition, avoids direct contact between aluminum powder and dispersant, suppresses side reactions that may be caused by the high activity of aluminum powder, and solves the problem of the aluminum electrolytic capacitor powder stacking sintered foil reacting with part of the solvent and the external environment during the preparation process. The aluminum electrolytic capacitor powder stacking sintered foil prepared after coating, degreasing treatment and sintering treatment has excellent electrostatic capacitance per unit area of ​​the aluminum electrolytic capacitor powder stacking sintered anode foil.

[0008] The first object of the present invention is to provide a method for preparing a powder stacked sintered foil of an aluminum electrolytic capacitor, comprising the following steps:

[0009] Aluminum powder and a dielectric substance precursor are used as raw materials, and a dielectric substance is deposited on the surface of the aluminum powder by chemical vapor deposition to obtain aluminum powder wrapped with the dielectric substance; the dielectric constant of the dielectric substance is greater than the dielectric constant of aluminum oxide.

[0010] Aluminum powder wrapped in dielectric material, a binder and a solvent are evenly mixed to obtain a slurry, which is then coated on an aluminum foil substrate. After drying, the slurry is degreased at 350°C to 550°C in an oxygen-containing atmosphere, and then sintered at 600°C to 670°C in an oxygen-free state. During the sintering process, the dielectric material combines with alumina to form a mixed dielectric layer. After the sintering is completed, the sintered foil is energized to obtain an aluminum electrolytic capacitor powder stack.

[0011] For example, the degreasing treatment temperature is 350°C, 400°C, 450°C, 500°C, 550°C, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0012] During the degreasing process, if the degreasing temperature is not high enough, carbon residue will be generated, resulting in powder sintering and accumulation, which will increase the leakage current of the anode foil.

[0013] During the sintering process, the sintering temperature is 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, etc., but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable. During the sintering process, the sintering atmosphere is any one or more of a vacuum atmosphere, an argon atmosphere, a nitrogen atmosphere, and a hydrogen atmosphere.

[0014] The drying temperature is 60°C to 150°C, and the drying time is 10min to 600min; the drying atmosphere is one or more of air atmosphere, vacuum atmosphere, argon atmosphere, and nitrogen atmosphere.

[0015] In a preferred embodiment of the present invention, the deposition thickness is 0.1 nm to 1200 nm. For example, the deposition thickness is 0.1 nm, 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, etc., but is not limited to the listed values, and other values ​​not listed within the above value range are also applicable.

[0016] In a preferred embodiment of the present invention, the slurry is composed of the following components in percentage by mass: 40% to 80% aluminum powder wrapped in a dielectric substance, 0.1% to 10% binder, and the rest is solvent, which is 100% in total.

[0017] For example, the aluminum powder coated with dielectric material is 40%, 50%, 60%, 70%, 80%, etc., the binder is 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., and the solvent is 10%, 20%, 30%, 40%, 50%, 59.9%, etc., but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0018] In a preferred embodiment of the present invention, double-sided coating is performed during coating, and the coating thickness of one side is 30 μm to 200 μm. For example, the thickness of the single-layer coating is 30 μm, 50 μm, 70 μm, 90 μm, 110 μm, 130 μm, 150 μm, 170 μm, 190 μm, 200 μm, etc., but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0019] The specific surface area of ​​the aluminum foil substrate is improved by coating thickness, thereby improving the electrostatic capacity of the aluminum electrolytic capacitor powder stacked sintered foil. The aluminum foil substrate used in the present invention has a purity of more than 99.5% and a thickness of between 20 μm and 50 μm.

[0020] In a preferred embodiment of the present invention, the heating rate of the degreasing treatment is 2°C / min to 20°C / min, and the time of the degreasing treatment is 0.5h to 15h. For example, the heating rate of the degreasing treatment is 2°C / min, 4°C / min, 6°C / min, 8°C / min, 10°C / min, 12°C / min, 14°C / min, 16°C / min, 18°C / min, 20°C / min, etc., and the time of the degreasing treatment is 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc., but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0021] In a preferred embodiment of the present invention, the heating rate of the sintering treatment is 2°C / min to 20°C / min, and the time of the sintering treatment is 0.5h to 15h. For example, the heating rate of the sintering treatment is 2°C / min, 4°C / min, 6°C / min, 8°C / min, 10°C / min, 12°C / min, 14°C / min, 16°C / min, 18°C / min, 20°C / min, etc., and the time of the degreasing treatment is 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc., but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0022] In a preferred embodiment of the present invention, the dielectric material is one or more of titanium dioxide, hafnium oxide, tantalum pentoxide, niobium oxide, barium titanate, strontium titanate, barium strontium titanate, lead zirconate titanate and bismuth ferrite. Typical but non-limiting examples of the combination include a combination of titanium dioxide and hafnium oxide, a combination of tantalum pentoxide and niobium oxide, a combination of barium titanate and strontium titanate, a combination of barium strontium titanate and lead zirconate titanate, a combination of bismuth ferrite and strontium titanate, etc., but are not limited to the listed values, and other values ​​not listed within the above numerical range are equally applicable.

[0023] In a preferred embodiment of the present invention, the binder is one or more of polyethylene oxide, hydroxypropyl cellulose, carboxymethyl cellulose, acrylic resin, and polypropylene carbonate. Typical but non-limiting examples of the combination include a combination of polyethylene oxide and hydroxypropyl cellulose, a combination of carboxymethyl cellulose and acrylic resin, a combination of polyethylene oxide and polypropylene carbonate, etc., but are not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0024] When preparing the slurry, the solvent is water, methanol, ethanol, terpineol, acetonitrile, acetone, dimethylformamide, N-methylpyrrolidone, n-butanol or methyl ethyl ketone.

[0025] In a preferred embodiment of the present invention, when chemical vapor deposition is performed, atomic layer deposition is used for preparation.

[0026] The second object of the present invention is to provide an aluminum electrolytic capacitor powder stacking sintered foil prepared by the above preparation method.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention deposits dielectric material on the surface of aluminum powder by vapor phase deposition, and deposits dielectric material on the surface of aluminum powder by controllable chemical vapor deposition method, thereby avoiding direct contact between aluminum powder and dispersant, inhibiting side reactions that may be caused by high activity of aluminum powder, and solving the problem of aluminum electrolytic capacitor powder stacking sintered foil reacting with part of solvent and external environment during preparation; after coating, sintering and energizing, a high dielectric composite powder stacking sintered anode foil for aluminum electrolytic capacitor is formed, further improving the electrostatic capacity of the unit area of ​​powder sintering stacked anode foil. The present invention adopts chemical vapor deposition method to make the dielectric material vapor phase coating layer on the surface of aluminum powder have high bonding strength and uniform thickness with aluminum powder, and is far superior to solid powder mixed coating and liquid phase coating. It solves the problem that nanoparticles fall off due to the mismatch of sintering temperature between aluminum powder and nano high dielectric constant particles after solid powder mixed coating, and the problem that the liquid phase coating layer cannot control thickness, resulting in excessive thickness of the coating layer, which affects carbon discharge and sintering neck formation during sintering. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 In the figure, a is a schematic diagram of aluminum powder, and b is a schematic diagram of the surface of aluminum powder coated with dielectric material.

[0030] Figure 2 Schematic diagram of dielectric material coated aluminum powder after sintering.

[0031] Reference numerals: 1 - dielectric substance, 2 - aluminum powder. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In view of the problems described in the background technology, the present invention provides a method for preparing a powder stacked sintered foil of an aluminum electrolytic capacitor, such as Figure 1 and Figure 2 As shown, during the preparation, aluminum powder 2 and a dielectric substance precursor are used as raw materials, and the dielectric substance 1 is deposited on the surface of the aluminum powder 2 by chemical vapor deposition to obtain aluminum powder coated with the dielectric substance.

[0034] Aluminum powder wrapped in dielectric material, binder and solvent are mixed evenly and coated on an aluminum foil substrate. After drying, degreasing treatment is carried out at 350°C to 550°C in an oxygen-containing atmosphere, and then sintering is carried out at 610°C to 670°C in an oxygen-free state. After sintering, energization is performed to obtain aluminum electrolytic capacitor powder stacking sintered foil.

[0035] The present invention introduces dielectric material 1 on the surface of aluminum powder 2 by chemical vapor deposition, and the dielectric material 1 on the surface of aluminum powder 2 has high bonding strength and uniform thickness, and is far superior to solid powder mixed coating and liquid phase coating. It solves the problem that the nanoparticles fall off due to the mismatch of sintering temperature between aluminum powder and nano high dielectric constant particles after solid powder mixed coating, and the coating layer is too thick due to the inability to control the thickness of the liquid phase coating layer, which affects the carbon discharge and the formation of sintering necks during the sintering process.

[0036] Dielectric substances exist stably in air and most solvents. After being coated by chemical vapor deposition, a dense protective layer is formed on the surface of aluminum powder, which effectively blocks the aluminum powder from reacting with the external environment due to its high activity, thereby reducing the activity of the aluminum powder. The dielectric substance precursor used in the vapor deposition process and the binder in the slurry contain a large amount of organic matter. They are subsequently sintered in a high-temperature oxygen-free environment to carbonize them, and the carbon residue will cause the leakage current of the powder sintered anode foil to increase. Therefore, firstly, high-temperature air heat treatment can effectively reduce the carbon residue in the powder sintered anode foil. Then, after high-temperature vacuum or inert atmosphere heat treatment and energizing treatment, the dielectric substance combines with alumina to form a mixed dielectric layer, which effectively increases the dielectric constant of the powder sintered anode foil, thereby increasing the electrostatic capacitance.

[0037] The average molecular weight of the polyethylene oxide used in the present invention is 10000, the average molecular weight of the hydroxypropyl cellulose is 40000, the average molecular weight of the carboxymethyl cellulose is 100000, the average molecular weight of the acrylic resin is 80000, the average molecular weight of the polyethylene oxide is 100000, and the average molecular weight of the polypropylene carbonate is 280000. The aluminum foil substrate used in the present invention has a purity of more than 99.5% and a thickness of 20-50 μm.

[0038] Example 1

[0039] Step (1), put aluminum powder with a particle size of 2-3 μm and a purity of 99.99% into an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, use nitrogen as a carrier gas, isopropyl titanate as a titanium source, and keep the titanium source temperature at 25°C, and pass it for 5 seconds, then pass nitrogen to purge for 30 seconds. Then pass O3 to react for 10 seconds, and then pass nitrogen to purge for 50 seconds. Repeat the deposition according to the above steps until the deposition thickness reaches 5nm, and obtain aluminum powder wrapped by dielectric material.

[0040] Step (2), weighing 60% of the aluminum powder coated with the dielectric material prepared in step (1), 3% of polyethylene oxide and 37% of ultrapure water by mass percentage, and mixing them evenly to obtain a slurry.

[0041] Step (3), coating the slurry prepared in step (2) onto an aluminum foil substrate, performing double-sided coating, with a coating thickness of 50 μm on one side, to obtain a powder-stacked coated foil.

[0042] Step (4), drying the powder-stacked coated foil prepared in step (3) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0043] Step (5), raising the temperature of the dried powder-stacked coated foil prepared in step (4) to 400°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours, to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0044] Example 2

[0045] Step (1), put aluminum powder with a particle size of 2-3 μm and a purity of 99.99% into an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, use nitrogen as a carrier gas, isopropyl titanate as a titanium source, and keep the titanium source temperature at 25°C, and pass it for 5 seconds, then pass nitrogen to purge for 30 seconds. Then pass O3 to react for 10 seconds, and then pass nitrogen to purge for 50 seconds. Repeat the deposition according to the above steps until the deposition thickness reaches 5nm, and obtain aluminum powder wrapped by dielectric material.

[0046] Step (2), weighing 60% of the aluminum powder coated with the dielectric material prepared in step (1), 0.6% of hydroxypropyl cellulose and 39.4% of anhydrous ethanol by mass percentage, and mixing them evenly to obtain a slurry.

[0047] Step (3), coating the slurry prepared in step (2) onto an aluminum foil substrate, performing double-sided coating with a single-sided coating thickness of 50 μm, to obtain a powder-stacked coated foil.

[0048] Step (4), drying the powder-stacked coated foil prepared in step (3) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0049] Step (5), raising the temperature of the dried powder-stacked coated foil prepared in step (4) to 500°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0050] Comparative Example 1

[0051] Step (1), weighing 60% of aluminum powder with a particle size of 2-3 μm and a purity of 99.99%, 3% of polyethylene oxide and 37% of ultrapure water by mass percentage, and mixing them evenly to obtain a slurry.

[0052] Step (2), coating the slurry prepared in step (1) onto an aluminum foil substrate, performing double-sided coating, with a coating thickness of 50 μm on one side, to obtain a powder-stacked coated foil.

[0053] Step (3), drying the powder-stacked coated foil prepared in step (2) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0054] Step (4), raising the temperature of the dried powder-stacked coated foil prepared in step (3) to 400°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0055] Comparative Example 2

[0056] Step (1), weighing 60% of aluminum powder with a particle size of 2-3 μm and a purity of 99.99%, 0.6% of hydroxypropyl cellulose and 39.4% of anhydrous ethanol by mass percentage, and mixing them evenly to obtain a slurry.

[0057] Step (2), coating the slurry prepared in step (1) onto an aluminum foil substrate, performing double-sided coating, with a coating thickness of 50 μm on one side, to obtain a powder-stacked coated foil.

[0058] Step (3), drying the powder-stacked coated foil prepared in step (2) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0059] Step (4), raising the temperature of the dried powder-stacked coated foil prepared in step (3) to 500°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours, to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0060] Example 3

[0061] Step (1), put aluminum powder with a particle size of 2-3 μm and a purity of 99.99% into an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, use nitrogen as a carrier gas, isopropyl titanate as a titanium source, and keep the titanium source temperature at 25°C, and pass it for 5 seconds, then pass nitrogen to purge for 30 seconds. Then pass O3 to react for 10 seconds, and then pass nitrogen to purge for 50 seconds. Repeat the deposition according to the above steps until the deposition thickness reaches 10nm, and obtain aluminum powder wrapped by dielectric material.

[0062] Step (2), weigh 60% of the aluminum powder coated with the dielectric material prepared in step (1), 3% of polyethylene oxide and 37% of ultrapure water according to mass percentage and mix them evenly to obtain a slurry.

[0063] Step (3), coating the slurry prepared in step (2) onto an aluminum foil substrate, performing double-sided coating, and the coating thickness on one side is 50 μm.

[0064] Step (4), drying the powder-stacked coated foil prepared in step (3) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0065] Step (5), raising the temperature of the dried powder-stacked coated foil prepared in step (4) to 400°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours, to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0066] Example 4

[0067] Step (1), put aluminum powder with a particle size of 2-3 μm and a purity of 99.99% into an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, use nitrogen as a carrier gas, isopropyl titanate as a titanium source, and keep the titanium source temperature at 25°C, and pass it for 5 seconds, then pass nitrogen to purge for 30 seconds. Then pass O3 to react for 10 seconds, and then pass nitrogen to purge for 50 seconds. Repeat the deposition according to the above steps until the deposition thickness reaches 10nm, and obtain aluminum powder wrapped by dielectric material.

[0068] Step (2), weighing 60% of the aluminum powder coated with the dielectric material prepared in step (1), 0.6% of hydroxypropyl cellulose and 39.4% of anhydrous ethanol in a ratio by mass and mixing them evenly to obtain a slurry.

[0069] Step (3), coating the slurry prepared in step (2) onto an aluminum foil substrate, performing double-sided coating with a single-sided coating thickness of 50 μm, to obtain a powder-stacked coated foil.

[0070] Step (4), drying the powder-stacked coated foil prepared in step (3) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0071] Step (5), raising the temperature of the dried powder-stacked coated foil prepared in step (4) to 500°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0072] Example 5

[0073] Step (1), put aluminum powder with a particle size of 4-5 μm and a purity of 99.99% into an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, use nitrogen as a carrier gas, TTIP as a titanium source, and keep the temperature of the titanium source at 25°C, and pass it for 5 seconds, then pass nitrogen to purge for 30 seconds. Then pass O3 to react for 10 seconds, and then pass nitrogen to purge for 50 seconds. Repeat the above steps for 200 times to obtain aluminum powder wrapped with dielectric material.

[0074] Step (2), weighing 60% of the aluminum powder coated with the dielectric material prepared in step (1), 3% of polyethylene oxide and 37% of ultrapure water by mass percentage, and mixing them evenly to obtain a slurry.

[0075] Step (3), coating the slurry prepared in step (2) onto an aluminum foil substrate, performing double-sided coating, with a coating thickness of 50 μm on one side, to obtain a powder-stacked coated foil.

[0076] Step (4), drying the powder-stacked coated foil prepared in step (3) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0077] Step (5), raising the temperature of the dried powder-stacked coated foil prepared in step (4) to 400°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours, to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0078] Example 6

[0079] Step (1), put aluminum powder with a particle size of 4-5 μm and a purity of 99.99% into an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, use nitrogen as a carrier gas, isopropyl titanate as a titanium source, and keep the titanium source temperature at 25°C, and pass it for 5 seconds, then pass nitrogen to purge for 30 seconds. Then pass O3 to react for 10 seconds, and then pass nitrogen to purge for 50 seconds. Repeat the deposition according to the above steps until the deposition thickness reaches 5nm, and obtain aluminum powder wrapped by dielectric material.

[0080] Step (2), weighing 60% of the aluminum powder coated with the dielectric material prepared in step (1), 0.6% of hydroxypropyl cellulose and 39.4% of anhydrous ethanol by mass percentage, and mixing them evenly to obtain a slurry.

[0081] Step (3), coating the slurry prepared in step (2) onto an aluminum foil substrate, performing double-sided coating, with a coating thickness of 50 μm on one side, to obtain a powder-stacked coated foil.

[0082] Step (4), drying the powder-stacked coated foil prepared in step (3) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0083] Step (5), raising the temperature of the dried powder-stacked coated foil prepared in step (4) to 500°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0084] Comparative Example 3

[0085] Step (1), weighing 60% of aluminum powder with a particle size of 4-5 μm and a purity of 99.99%, 3% of polyethylene oxide and 37% of ultrapure water by mass percentage, and mixing them evenly to obtain a slurry.

[0086] Step (2), coating the slurry prepared in step (1) onto an aluminum foil substrate, performing double-sided coating, with a coating thickness of 50 μm on one side, to obtain a powder-stacked coated foil.

[0087] Step (3), drying the powder-stacked coated foil prepared in step (2) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0088] Step (4), sintering the dried powder stacked coated foil prepared in step (3), raising the temperature to 400°C at a heating rate of 10°C / min and maintaining it for 1 hour in an air atmosphere; then raising the temperature to 640°C at a heating rate of 10°C / min and maintaining it for 4 hours in a vacuum state to obtain an aluminum electrolytic capacitor powder stacked sintered foil.

[0089] Comparative Example 4

[0090] Step (1), weighing 60% of aluminum powder with a particle size of 4-5 μm and a purity of 99.99%, 0.6% of hydroxypropyl cellulose and 39.4% of anhydrous ethanol by mass percentage, and mixing them evenly to obtain a slurry.

[0091] Step (2), coating the slurry prepared in step (1) onto an aluminum foil substrate, performing double-sided coating, with a coating thickness of 50 μm on one side, to obtain a powder-stacked coated foil.

[0092] Step (3), drying the powder-stacked coated foil prepared in step (2) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0093] Step (4), raising the temperature of the dried powder-stacked coated foil prepared in step (3) to 500°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours, to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0094] Example 7

[0095] Step (1), put aluminum powder with a particle size of 4-5 μm and a purity of 99.99% into an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, use nitrogen as a carrier gas, isopropyl titanate as a titanium source, and keep the titanium source temperature at 25°C, and pass it for 5 seconds, then pass nitrogen to purge for 30 seconds. Then pass O3 to react for 10 seconds, and then purge nitrogen for 50 seconds. Repeat the above steps until the deposition thickness reaches 10nm, and obtain aluminum powder wrapped by dielectric material.

[0096] Step (2), weighing 60% of the aluminum powder coated with the dielectric material prepared in step (1), 0.6% of polyethylene oxide and 39.4% of ultrapure water by mass percentage, and mixing them evenly to obtain a slurry.

[0097] Step (3), coating the slurry prepared in step (2) onto an aluminum foil substrate, performing double-sided coating, with a coating thickness of 50 μm on one side, to obtain a powder-stacked coated foil.

[0098] Step (4), drying the powder-stacked coated foil prepared in step (3) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0099] Step (5), raising the temperature of the dried powder-stacked coated foil prepared in step (4) to 400°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours, to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0100] Example 8

[0101] Step (1), put aluminum powder with a particle size of 4-5 μm and a purity of 99.99% into an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, use nitrogen as a carrier gas, isopropyl titanate as a titanium source, and keep the titanium source temperature at 25°C, and pass it for 5 seconds, then pass nitrogen to purge for 30 seconds. Then pass O3 to react for 10 seconds, and then pass nitrogen to purge for 50 seconds. Repeat the above steps until the deposition thickness reaches 10nm, and obtain aluminum powder wrapped by dielectric material.

[0102] Step (2), weighing 60% of the aluminum powder coated with the dielectric material prepared in step (1), 0.6% of hydroxypropyl cellulose and 39.4% of anhydrous ethanol by mass percentage, and mixing them evenly to obtain a slurry.

[0103] Step (3), coating the slurry prepared in step (2) onto an aluminum foil substrate, performing double-sided coating with a single-sided coating thickness of 50 μm, to obtain a powder-stacked coated foil.

[0104] Step (4), drying the powder-stacked coated foil prepared in step (3) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0105] Step (5), raising the temperature of the dried powder-stacked coated foil prepared in step (4) to 500°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0106] Example 9

[0107] Step (1), put aluminum powder with a particle size of 4-5 μm and a purity of 99.99% into an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, use nitrogen as a carrier gas, isopropyl titanate as a titanium source, and keep the titanium source temperature at 25°C, and pass it for 5 seconds, then pass nitrogen to purge for 30 seconds. Then pass O3 to react for 10 seconds, and then pass nitrogen to purge for 50 seconds. Repeat the above steps until the deposition thickness reaches 10nm, and obtain aluminum powder wrapped by dielectric material.

[0108] Step (2), weighing 80% of the aluminum powder coated with the dielectric material prepared in step (1), 10% of the composite binder and 10% of water by mass percentage, and mixing them evenly to obtain a slurry. The composite binder is polyoxyethylene and hydroxymethyl cellulose in a mass ratio of 1:1.

[0109] Step (3), coating the slurry prepared in step (2) onto an aluminum foil substrate, performing double-sided coating with a single-sided coating thickness of 80 μm, to obtain a powder-stacked coated foil.

[0110] Step (4), drying the powder-stacked coated foil prepared in step (3) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0111] Step (5), raising the temperature of the dried powder stacking coated foil prepared in step (4) to 350°C at a heating rate of 10°C / min and degreasing it in an air atmosphere for 1 hour; then raising the temperature to 670°C at a heating rate of 10°C / min, sintering it in a vacuum state for 4 hours, and obtaining a powder stacking sintered foil for an aluminum electrolytic capacitor.

[0112] Example 10

[0113] Step (1), put aluminum powder with a particle size of 2-3 μm and a purity of 99.99% into an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, use nitrogen as a carrier gas, isopropyl titanate as a titanium source, and keep the titanium source temperature at 25°C, and pass it for 5 seconds, then pass nitrogen to purge for 30 seconds. Then pass O3 to react for 10 seconds, and then pass nitrogen to purge for 50 seconds. Repeat the deposition according to the above steps until the deposition thickness reaches 5nm, and obtain aluminum powder wrapped by dielectric material.

[0114] Step (2), weighing 40% of the aluminum powder coated with the dielectric material prepared in step (1), 0.1% of polyethylene oxide and 59.9% of ultrapure water by mass percentage, and mixing them evenly to obtain a slurry.

[0115] Step (3), coating the slurry prepared in step (2) onto an aluminum foil substrate, performing double-sided coating, with a coating thickness of 50 μm on one side, to obtain a powder-stacked coated foil.

[0116] Step (4), drying the powder-stacked coated foil prepared in step (3) in an air atmosphere at 100° C. for 30 minutes to obtain a dried powder-stacked coated foil.

[0117] Step (5), raising the temperature of the dried powder-stacked coated foil prepared in step (4) to 400°C at a heating rate of 10°C / min, degreasing it in an air atmosphere, and maintaining the degreasing time for 1 hour; then raising the temperature to 640°C at a heating rate of 10°C / min, sintering it in a vacuum state, and maintaining the sintering time for 4 hours, to obtain an aluminum electrolytic capacitor powder-stacked sintered foil.

[0118] The aluminum capacitor sintered foils prepared in Examples 1 to 8 of the present invention and Comparative Examples 1 to 4 were formed in a boric acid system solution according to standard SJ / T11140-2022, with a forming voltage of 500 and 700 V and a current density of 0.5 A / cm 2 Then, the electrostatic capacitance was tested in 80 g / L ammonium pentaborate solution, and the withstand voltage was tested in 70 g / L boric acid solution. The results are described in Table 1 below.

[0119] Table 1 Experimental results

[0120]

[0121]

[0122] It should be noted that “—” means that the condition was not tested.

[0123] As can be seen from Table 1, the withstand voltage values ​​of Comparative Examples 1 to 4 and Examples 1 to 8 are all higher than the preset forming voltage. Compared with the electrostatic capacitance and withstand voltage of the aluminum powder sintered stacked foil anode in Comparative Examples 1 to 4, the electrostatic capacitance and withstand voltage of the high dielectric constant powder sintered stacked foil anode prepared by high dielectric constant coated aluminum powder in Examples 1-8 of the present invention are significantly improved, indicating that the introduction of dielectric substances, after high-temperature heat treatment and empowerment, effectively improves the dielectric constant of the anode, thereby improving the electrostatic capacitance. In Example 1, Example 3, Example 5 and Example 7, compared with the use of organic solvents to prepare aluminum electrolytic capacitor powder sintered stacked anode foil, the aluminum electrolytic capacitor powder sintered stacked anode foil prepared with ultrapure water as solvent has significantly improved electrostatic capacitance and withstand voltage, indicating that the aluminum powder coated with high dielectric constant is passivated after coating, inhibiting the side reactions that may be caused by the high activity of aluminum powder, and solving the problem of the reaction of the highly active aluminum powder with some solvents and the external environment during the preparation of the aluminum electrolytic capacitor powder stacked sintered foil.

[0124] The present invention reduces the activity of aluminum powder by introducing a dielectric material deposition layer greater than aluminum oxide on the surface of aluminum powder, expands the selection range of binders and dispersants, and further improves the static capacitance of the powder sintered anode foil. The thickness of the deposition layer formed by the chemical vapor deposition method is uniform and controllable, and different deposition thicknesses can be selected according to different withstand voltage sections; the coated aluminum powder has a stable deposition layer on the surface, which can effectively prevent the aluminum powder from reacting with the outside air and water, reduce the generation of amorphous aluminum oxide, and retain the aluminum core part to a greater extent, thereby helping to improve the static capacitance. At the same time, the safety factor is greatly improved when the water system is stirred.

[0125] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0126] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a powder-stacked sintered foil for an aluminum electrolytic capacitor, characterized in that: The following steps are involved: Aluminum powder and a dielectric substance precursor are used as raw materials, and a high dielectric substance is deposited on the surface of the aluminum powder by chemical vapor deposition to obtain aluminum powder coated with the dielectric substance; the dielectric constant of the dielectric substance is greater than the dielectric constant of aluminum oxide; Aluminum powder wrapped in dielectric material, a binder and a solvent are evenly mixed to obtain a slurry, which is then coated on an aluminum foil substrate. After drying, the slurry is degreased at 350°C to 550°C in an oxygen-containing atmosphere, and then sintered at 600°C to 670°C in an oxygen-free state. During the sintering process, the dielectric material combines with alumina to form a mixed dielectric layer. After the sintering is completed, the sintered foil is energized to obtain an aluminum electrolytic capacitor powder stack.

2. The method for preparing a powder stacked sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The deposition thickness is 0.1nm~1200nm.

3. The method for preparing a powder stacked sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The slurry is composed of the following components in percentage by mass: 40% to 80% of aluminum powder wrapped by dielectric material, 0.1% to 10% of binder, and the rest of solvent, which is 100% in total.

4. The method for preparing a powder-stacked sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: During coating, double-sided coating is performed, and the coating thickness on one side is 30 μm to 200 μm.

5. The method for preparing a powder-stacked sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The heating rate of the degreasing treatment is 2°C / min to 20°C / min, and the time of the degreasing treatment is 0.5h to 15h.

6. The method for preparing a powder-stacked sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The heating rate of the sintering treatment is 2°C / min to 20°C / min, and the sintering treatment time is 0.5h to 15h.

7. The method for preparing a powder-stacked sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The dielectric material is one or more of titanium dioxide, hafnium oxide, tantalum pentoxide, niobium oxide, barium titanate, strontium titanate, barium strontium titanate, lead zirconate titanate, and bismuth ferrite.

8. The method for preparing a powder-stacked sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The binder is one or more of polyethylene oxide, hydroxypropyl cellulose, carboxymethyl cellulose, acrylic resin or polypropylene carbonate; The solvent is water, methanol, ethanol, terpineol, acetonitrile, acetone, N,N-dimethylformamide, N-methylpyrrolidone, n-butanol or methyl ethyl ketone.

9. The method for preparing a powder-stacked sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: Chemical vapor deposition is an atomic layer deposition method.

10. A powder stacked sintered foil of an aluminum electrolytic capacitor prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for manufacturing anode foil of aluminum electrolytic capacitor with high dielectric constant composite film

    CN117373830B

  • Aluminum electrolytic capacitor anode sintered foil and preparation method thereof

    CN117594359B

  • High voltage resistant supercapacitor electrode pole piece as well as preparation method and application thereof

    CN106298262A

  • Nano dielectric powder coated aluminum electrolytic capacitor sintered foil and preparation method thereof

    CN115188598A

  • Electrode foil and preparation method thereof, capacitor and electronic device

    CN115376828A

Cited By

  • Anode foil material for electrolytic capacitor and preparation method and application thereof

    CN120565296A

  • Large-ripple-current-resistant sintered anode foil, preparation method thereof and electrolytic capacitor

    CN122000205A

  • A sintered anode foil resistant to high ripple current and its preparation method, and an electrolytic capacitor.

    CN122000205B